Três estudos de concerto para violão de Radamés Gnattali peculiaridades estilísticas e suas implicações com processos de circularidade cultural - Silva, Valdemar Alves (2014)
This research aimed to investigate the technical characteristics/stylistic involved with the Three Studies of Concert for guitar the songwriter gaucho Radamés Gnattali, in its interaction with the processes of circularity and cultural hybridization. Tried to reach, especially, to the peculiarities of the work of this composer, related to the inseparability between stylistic characteristics /idiomatismo/Technical/cultural interaction, emphasizing always transit that has been established between the specificities of different fields of musical production (Bourdieu, 2003). Chartier (1990), Hall (2005), Bourdieu (2003) and Canclini offered (2003), allowed for a theoretical foundation that took on important representational reference, referring to the possibilities raised by practical knowledge and daily involved with identitary processes, that is the objective and becomes evident in verbal formulations, practices and cultural works. This reasoning pointed as the methodological approach, in addition to the bibliographic research, referring to the removal of scenarios sociohistorical and cultural and the elements of the path of life and musical Gnattali, the analysis and interpretation of works that integrate the Three Studies of Concert for guitar. In this context, the analysis and interpretation of scores were performed in interaction with the analysis and interpretation of works recorded on CDs and with data collected in the research literature. Thus, it was possible to confirm the assumption that the works of Radamés Gnatalli Gnattali that integrate Three studies of Concert for guitar, were able to prove the specificity of his work as a composer, a composer who transitioned so fluidic flip by different cultural dimensions; who worked in the most peculiar way a musical language hybrid, indicative of stylistic peculiarities that demonstrate not only his transit cultural, but also their interaction with the sound features, technicians of the instrument.